1991
DOI: 10.1161/01.res.69.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial contractile actions of endothelin-1 in rat and rabbit papillary muscles. Role of endocardial endothelium.

Abstract: The actions of endothelin on the contractile and twitch configuration characteristics of rat and rabbit papillary muscles were evaluated before and after endocardial endothelium removal. In rabbit papillary muscles, endothelin produced a dose-dependent (10(-11) to 10(-7) M) increase in tension (T) (from 2.7 +/- 0.2 to 8.9 +/- 0.7 g/mm2, p less than 0.01), dT/dt, and Vmax (from 1.14 +/- 0.03 to 3.0 +/- 0.13 Lmax/sec, p less than 0.01), a decrease in time to peak tension (from 251 +/- 9 to 216 +/- 7 msec, p less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 38 publications
0
40
1
1
Order By: Relevance
“…Direct positive inotropic effects of ET-1 have been described in rat, rabbit, and ferret [3][4][5][6][7] but not in guinea pig 8 or dog 6 myocardium. Recently, a direct inotropic effect of ET-1 has been reported for human atrial myocardium, 26 and a single concentration of ET-1 showed inotropic responses in muscle strips 18 and isolated myocytes 17 from failing human hearts.…”
Section: Functional Effects Of Et-1mentioning
confidence: 98%
See 1 more Smart Citation
“…Direct positive inotropic effects of ET-1 have been described in rat, rabbit, and ferret [3][4][5][6][7] but not in guinea pig 8 or dog 6 myocardium. Recently, a direct inotropic effect of ET-1 has been reported for human atrial myocardium, 26 and a single concentration of ET-1 showed inotropic responses in muscle strips 18 and isolated myocytes 17 from failing human hearts.…”
Section: Functional Effects Of Et-1mentioning
confidence: 98%
“…1 In addition, ET-1 acts as a growth factor inducing hypertrophy. 2 Furthermore, ET-1 exerts positive inotropic effects in rat, 3,4 rabbit, 5,6 and ferret 7 but not in guinea pig 8 or dog 6 myocardium. Recently, a local ET production in the heart has been demonstrated; it is secreted from the endocardium, the myocardium, and the coronary endothelium, 9,10 thereby acting in a paracrine and autocrine fashion on myocytes.…”
mentioning
confidence: 98%
“…( 15,17,(22)(23)(24)(25) in which a number of well-documented phenotypic changes occur during adaptation to primary culture. Importantly, by [7][8][9][10] (26,27), emphasizing the importance of using tissue-specific endothelium for in vitro models where appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular and endocardial endothelial cells are a potential source ofthese and other peptide cytokines, as well as a number of additional compounds ofdisparate biological activity that maydirectly or indirectly affect the function of adjacent cardiac muscle cells (4,5). Since the initial reports by Brutsaert and co-workers (6,7), several groups have now confirmed that endocardial endothelium can regulate the inotropic response ofsubjacent myofibrils (8,9) and that the function of contractile proteins within ventricular muscle may be regulated by factors released from the microvasculature (10,11).…”
Section: Introductionmentioning
confidence: 95%
“…In isolated muscle preparations, ET-1 elicits a dose-dependent (0.1, 1 and 10 nM) acceleration of the rate of tension decline (increased dT/dt min ) [33,38]. To understand the physiologic mechanisms of this positive lusitropic effect, studies were performed in isolated rabbit papillary muscles.…”
Section: The Effects Of Et-1 On Myocardial Relaxationmentioning
confidence: 99%